Type material of Acanthocephala, Nematoda and other non-helminths phyla (Cnidaria, Annelida, and Arthropoda) housed in the Helminthological Collection of the Oswaldo Cruz Institute/ FIOCRUZ (CHIOC), Rio de Janeiro, Brazil, from 1979 to 2016 - Lopes, Daniela A. (2017)
Fundação Oswaldo Cruz. Instituto Oswaldo Cruz. Laboaratório de Helmintos Parasitos de Vertebrados. Rio de Janeiro, RJ, Brasil